English Teachers’ TPACK Level, Factors, and the Impacts in Vocational High School - Destiani, Isti; Setyarini, Sri; Rodliyah, Rojab Siti (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2022)
This study is aimed to investigate English teachers’ TPACK level and explore its impact on teaching English to Vocational high school students in Garut. In this mixed-method study, questionnaires, interviews, and observation were used as the instruments for collecting the data. The participants of this study were 50 vocational high school English teachers in Garut. After collecting the data from the questionnaire, this study showed various results for each domain. On average, more than 60% of the participants had a high level of TPACK. And the rest of them had an adequate and low level of TPACK. In addition, based on the interview, factors that influenced the differences in TPACK level among the participants were divided into three aspects: technology, pedagogy, and content knowledge. Factors that influence the technology aspects were facilities, technology mastery, and willingness and curiosity. Meanwhile, factors of pedagogy are influenced by teaching experience and strategy, training, and certification from the government. Whereas, factors of content knowledge are caused by educational background, age, and English knowledge mastery. Thus, English teachers with TPACK levels impact their teaching practices in vocational high schools. Most of them applied technology in the classroom, such as using laptops, projectors, audio and video file, PowerPoint, and digital book. Besides, they also used many teaching strategies with English knowledge mastery in teaching so that their students were more enthusiastic about learning English. This study is expected to benefit the teachers as they derive relevant details for their development and professionalism